1995
DOI: 10.1007/bf02064200
|View full text |Cite
|
Sign up to set email alerts
|

Choledocholithiasis in patients with normal serum liver enzymes

Abstract: Retrospective chart review of 330 patients undergoing ERCP over a two-year period yielded five patients with choledocholithiasis whose serum liver enzyme and total bilirubin levels were repeatedly normal. All were female, three were elderly, and the gallbladder was in situ in three of the five, one of whom had a large gallbladder remnant. In four patients, the common bile duct was dilated (> 10 mm), whereas none had intrahepatic duct dilatation. Four patients had a prominent ampulla, and stone size varied wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Interestingly, four (0.5%) patients in the ACC/CDL group had no aminotransferase derangement even in the presence of a known CBD stone. This phenomenon has been observed in the past 30 . We do not know why a vast majority of patients have liver enzyme abnormalities, reflecting biliary obstruction, while a few do not.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, four (0.5%) patients in the ACC/CDL group had no aminotransferase derangement even in the presence of a known CBD stone. This phenomenon has been observed in the past 30 . We do not know why a vast majority of patients have liver enzyme abnormalities, reflecting biliary obstruction, while a few do not.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, a strict reliance on blood chemistry will lead to disappointments in predicting its presence. In fact, normal liver enzymes in the presence of CBDS are well reported [52].…”
Section: Blood Chemistrymentioning
confidence: 96%
“…Several older studies note the presence of normal liver tests in a small percentage of patients but did not characterize these patients further [6,7,8]. To our knowledge, there has been only one prior study specifically addressing normal liver chemistry tests in patients with choledocholithiasis [15]. This retrospective study of 330 patients undergoing ERCP identified 5 patients in whom these tests were repeatedly normal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, abnormal liver chemistry tests are considered the hallmark of CBD stones. While CBD stones may be found in an asymptomatic patient, there is little information on the prevalence of normal liver chemistry tests in patients with CBD stones [15] and to our knowledge no data on associated risk factors. Such information could be useful for patients undergoing laparoscopic cholecystectomy as well as expanding the spectrum of clinical presentation of such patients.…”
Section: Introductionmentioning
confidence: 99%